2021
DOI: 10.1038/s41467-021-23890-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting lapses of attention with sleep-like slow waves

Abstract: Attentional lapses occur commonly and are associated with mind wandering, where focus is turned to thoughts unrelated to ongoing tasks and environmental demands, or mind blanking, where the stream of consciousness itself comes to a halt. To understand the neural mechanisms underlying attentional lapses, we studied the behaviour, subjective experience and neural activity of healthy participants performing a task. Random interruptions prompted participants to indicate their mental states as task-focused, mind-wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 98 publications
13
82
0
Order By: Relevance
“…The possibility of non-invasive modulation of sleep oscillations has recently attracted significant attention (Bellesi, Riedner, Garcia-Molina, Cirelli, & Tononi, 2014; Choi, Kwon, & Jun, 2020; Fattinger et al, 2019; Frase et al, 2019; Geiser et al, 2020; Krugliakova et al, 2022; Malkani & Zee, 2020; Marshall, Helgadottir, Molle, & Born, 2006; Ngo, Martinetz, Born, & Molle, 2013; Schneider, Lewis, Koester, Born, & Ngo, 2020). Slow waves are a predominant type of sleep oscillatory activity during NREM sleep, but can also occur during REM sleep and wakefulness (Andrillon, Burns, Mackay, Windt, & Tsuchiya, 2021; Bernardi et al, 2019; Borbely, Tobler, & Hanagasioglu, 1984; Funk, Honjoh, Rodriguez, Cirelli, & Tononi, 2016; Vyazovskiy et al, 2014; Vyazovskiy et al, 2011). Sleep slow waves are homeostatically regulated (Achermann, Dijk, Brunner, & Borbely, 1993; Borbély, 1982; Huber, Deboer, & Tobler, 2000; Krone et al, 2021; Thomas, Guillaumin, McKillop, Achermann, & Vyazovskiy, 2020), and have been implicated in synaptic plasticity, metabolic restoration, glymphatic clearance and other functions (Frank & Heller, 2019; James M. Krueger, Frank, Wisor, & Roy, 2016; Vyazovskiy & Harris, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of non-invasive modulation of sleep oscillations has recently attracted significant attention (Bellesi, Riedner, Garcia-Molina, Cirelli, & Tononi, 2014; Choi, Kwon, & Jun, 2020; Fattinger et al, 2019; Frase et al, 2019; Geiser et al, 2020; Krugliakova et al, 2022; Malkani & Zee, 2020; Marshall, Helgadottir, Molle, & Born, 2006; Ngo, Martinetz, Born, & Molle, 2013; Schneider, Lewis, Koester, Born, & Ngo, 2020). Slow waves are a predominant type of sleep oscillatory activity during NREM sleep, but can also occur during REM sleep and wakefulness (Andrillon, Burns, Mackay, Windt, & Tsuchiya, 2021; Bernardi et al, 2019; Borbely, Tobler, & Hanagasioglu, 1984; Funk, Honjoh, Rodriguez, Cirelli, & Tononi, 2016; Vyazovskiy et al, 2014; Vyazovskiy et al, 2011). Sleep slow waves are homeostatically regulated (Achermann, Dijk, Brunner, & Borbely, 1993; Borbély, 1982; Huber, Deboer, & Tobler, 2000; Krone et al, 2021; Thomas, Guillaumin, McKillop, Achermann, & Vyazovskiy, 2020), and have been implicated in synaptic plasticity, metabolic restoration, glymphatic clearance and other functions (Frank & Heller, 2019; James M. Krueger, Frank, Wisor, & Roy, 2016; Vyazovskiy & Harris, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of non-invasive modulation of sleep oscillations has recently attracted significant attention (Bellesi, Riedner, Garcia-Molina, Cirelli, & Tononi, 2014;Choi, Kwon, & Jun, 2020;Fattinger et al, 2019;Frase et al, 2019;Geiser et al, 2020;Krugliakova et al, 2022;Malkani & Zee, 2020;Marshall, Helgadottir, Molle, & Born, 2006;Ngo, Martinetz, Born, & Molle, 2013;Schneider, Lewis, Koester, Born, & Ngo, 2020). Slow waves are a predominant type of sleep oscillatory activity during NREM sleep, but can also occur during REM sleep and wakefulness (Andrillon, Burns, Mackay, Windt, & Tsuchiya, 2021; Bernardi paradigms likely leads to many instances when stimulation is delivered during a suboptimal or even undesirable phase of the network oscillation. Arguably, this could influence the outcome of modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the high quality and high-density EEG (60-256 channels) are more and more adopted in sleep research in both healthy and clinical populations. Higher spatial resolution in EEG has led to discoveries that have reshaped our conceptualization of sleep physiology, with the characterization of NREM slow waves as travelling waves (38), the identification of two types of NREM slow waves (39), the presence of slow waves in REM sleep (40) and even in wakefulness (41), or the identification of inter-hemispheric differences in slow wave activity (42). This recent research has revealed the importance of the local aspects of sleep (43).…”
Section: Refining Traditional Sleep Stagesmentioning
confidence: 99%
“…For example, by identifying distinct feature patterns in ongoing EEG, sleeping participants can be awakened and asked to report their conscious experience (62,63). Likewise, wakeful subjects can be asked to report their ongoing thoughts (41,67). This reversal of analysis from brain to phenomenology is technically more demanding, but it is one of the holy grails of neuroscience.…”
Section: Future Implicationsmentioning
confidence: 99%
“…Lapses of attention during different tasks are not only caused by mind wandering. In fact, moments of distraction can be also by caused by drowsiness, fatigue or 'mind blanking' (Andrillon et al, 2019(Andrillon et al, , 2021. However, these other factors are typically not assessed directly in studies investigating the EEG correlates of meditation practice.…”
Section: Introductionmentioning
confidence: 99%